Construction and Analysis of an LncRNA-miRNA-mRNA Network Based on Competitive Endogenous RNA Reveal miRNAs Potentially Involved in In-stent Restenosis after Percutaneous Coronary Intervention - Xiao Jin; Bingxin Wu; Li Han; Xiaofeng Zhu (Cardiology Discovery)
Objective:. Percutaneous coronary intervention is one of the most common procedures used for the invasive treatment of patients with coronary heart disease; the incidence of in-stent restenosis (ISR) after percutaneous coronary intervention is 5% to 15%. In this study, a competitive endogenous RNA (ceRNA) network was constructed to investigate potential mechanisms involved in ISR. Methods:. The expression data for differentially expressed microRNAs (DEmiRNAs) and messenger RNAs (mRNAs) between patients with and without ISR were obtained using limma package. Long noncoding RNAs (lncRNAs) were predicted based on the DEmiRNAs using the miRDB, miRTarBase, and TargetScan databases. An ISR-specific ceRNA network was subsequently constructed and investigated. To verify the key miRNAs of ceRNA, patients with and without ISR were enrolled from Guangdong Provincial Hospital of Chinese Medicine between January 2017 and December 2018 (n = 8, respectively); plasma was collected from all enrolled patients. Results:. Based on the raw data obtained from the Gene Expression Omnibus database, 472 DEmiRNAs and 304 differentially expressed messenger RNAs between patients with and without ISR were identified. A ceRNA network was constructed by combining 270 lncRNAs, 3 miRNAs (miR-125, miR-140, and miR-206), and 4 mRNAs (STRADB, TKT, PCTP, and BTG2). The hub genes of the ceRNA network of ISR included the following: miR-125, miR-206, miR-140, PCDHB9, CASC2, BAK1P1, CSPG4P3Y, CSPG4P4Y, STRCP1, and GRIP2. Verification of miRNAs of ceRNA also showed that the expression of miR-206 was upregulated in patients with ISR vs. those without ISR (P < 0.05). In contrast, the expression of miR-140 and miR-125 was downregulated in patients with ISR vs. those without ISR (P < 0.05). Conclusions:. This study constructed noncoding RNA-related ceRNA networks for ISR. The results indicated that miR-206, miR-125, and miR-140 may be biomarkers of ISR.